SURVEY ON TREATMENT ADHERENCE AND RELATED FACTORS IN PATIENTS WITH ENDOPHTHALMITIS AT THE VITREORETINAL DEPARTMENT, HO CHI MINH CITY EYE HOSPITAL, 2024-2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: The study titled survey on treatment adherence and related factors among patients with endophthalmitis at the Vitreoretinal Department, Ho Chi Minh city Eye Hospital to evaluate and improve treatment effectiveness.Method: The study utilized the MMAS-8 scale (Cronbach’s Alpha = 0.83) to measure medication adherence behavior and a non-medication adherence questionnaire (Cronbach’s Alpha = 0.7) to assess non-medication adherence.Results: The medication adherence rate was 82.7% (MMAS-8 score ≥ 6), while the non-medication adherence rate was 65.3% (score ≥ 8/10). The study found that medication adherence was associated with occupation (civil servants were 1.3 times more adherent than farmers), educational level (those who were literate had 41% lower adherence, and those with primary education had 32% lower adherence compared to the illiterate group), and comorbidities (patients with asthma/COPD were 1.49 times more adherent than those without).Conclusion: The study provides a foundation for improving adherence guidance and enhancing treatment quality in the Vitreoretinal Department, Ho Chi Minh city Eye Hospital.
Keywords: Endophthalmitis, treatment adherence, medication, non-medication, MMAS-8.